Elevated Intracranial Pressure as a Cause of Sick Sinus Syndrome - Samer Makhaly; Parvaneh Fallah; Nadia Giannetti (Case Reports in Cardiology)
Sick sinus syndrome (SSS) has multiple causes both familial and acquired. The most common cause is usually idiopathic. In the past literature, elevated intracranial pressure (ICP) has not been reported to be a cause of SSS. We present a case of a 55-year-old male that developed SSS after surgical resection of a brain tumor. We have investigated the causal relationship between increased ICP and SSS. We have concluded that elevated ICP creates a sympathovagal imbalance leading to SSS.